Autofiction: Mock Theoryor Disfigurement of a Genre - Diaconu, Diana (Universidad Pedagógica y Tecnológica de Colombia, 2017)
Theaimofthiscontributionistoprovideacriticaloverviewofthecurrentstateofreflectiononautofictionin HispanicAmerica.WiththispurposeIlocateandanalyzethemainclichésintheoreticalandcriticalproposals about autofiction today, attempting to demonstrate the ways in which they distort the current landscape of autofictional theory, still under construction. The task of censoring the clichés of criticism implies analyzing erroneous readings which tend to blur fundamental statements about the nature of autofiction, while rescuing the essential meanings that have been neglected or mystified. Finally, I point out some future challenges for criticism, based on unexplored or prematurely abandoned directions which I consider to be valuablefor a theory of autofiction. To recover the sociocultural perspective, which inquires into the meaning of the genre, will also make it possible to analyze the particularities of the genre in Latin America; an urgent and crucial task for contemporary theory andliterarycriticism.